Behavior of elementary schoolchildren with iron deficiency anemia after iron therapy - Rina A.C. Saragih; T. Mirda Zulaicha; Sri Sofyani; Bidasari Lubis; Iskandar Z. Lubis (Indonesian Pediatric Society, 2009)
Background Some studies had been performed to determine theassociation between iron status and children's behavior yet it isstill controversial.Objective To investigate whether iron therapy has an effect onthe behavior of children with iron deficiency anemia (IDA).Method A randomized placebo-controlled clinical trial wasconducted in Labuhan Batu on November 2006-April2007. IDAwas defined as Hb < 12 g/dl, MCHC< 31%, ROW index > 220and Mentzer index> 13. Elementary school children (6-12 yearsold) with IDA were randomly assigned to the treatment groupwith a daily therapy of 6 mg iron/kg/day or placebo group for three months. The subjects' behavior was evaluated with child behavior check list (CBCL) before and six months after intervention.Results After six months, 110 subjects completed the therapy.Scores of CBCL in iron group after intervention were internalizing42.64 (SO 9.95), externalizing 37.13 (SO 9.04) & total score 38.24 (SO 10.20). There was significant decreased on externalizing and total problems score in the treatment group after intervention (P< 0.05). However, there was no significant difference on scores between groups.Conclusion Iron therapy had significantly decrease CBCL scoreon externalizing and total problems in the treatment group,however there was no significant difference on scores if comparedwith placebo group.